KEBUTUHAN PERAWATAN ORTODONTI BERDASARKAN INDEX OF ORTHODONTIC TREATMENT NEED PADA USIA REMAJA 15 – 17 TAHUN - Oley, Axel B.; Anindita, P. S.; Leman, Michael A. (e-GiGi, 2015)
Abstract: Dental and oral health is an important factor that must be maintained. Things that affect dental health problems and oral one of them is malocclusion. The application needs orthodontic treatment is aimed at correcting malocclusions that can affect the health of the teeth and oral cavity as well as the appearance of a person's face. Research conducted a descriptive study. The purpose of this study to determine the needs of orthodontic treatment based Index of Orthodontic Treatment Need (IOTN), which consists of two components, namely the Aesthetic Component (AC) and the Dental Health Component (DHC). The study was conducted in high school 3 Tondano country with the number of students 390 people. Data collection was performed by inspection and measurement using the AC and DHC. The results showed that 85.94% based on the air-conditioning was not / little need of treatment, 9.37% needed treatment and of 4.69% borderline desperate need of care, while 51.56% based DHC no / little need of treatment, 35.94% need treatment of borderline and 12.5% in dire need of treatment.Keywords: malocclusion, Index of Orthodontic Treatment Need, Aesthetic Component, Dental Health Component.Abstrak: Kesehatan gigi dan rongga mulut merupakan faktor penting yang harus dijaga. Hal yang mempengaruhi masalah kesehatan gigi dan rongga mulut salah satunya ialah maloklusi.Penerapan kebutuhan perawatan ortodonti ditujukan untuk memperbaiki maloklusi yang dapat mempengaruhi kesehatan gigi dan rongga mulut serta penampilan wajah seseorang.Penelitian yang dilakukan merupakan suatu penelitian yang bersifat deskriptif.Tujuan dari penelitian ini untuk mengetahui kebutuhan perawatan ortodonti berdasarkan Index of Orthodontic Treatment Need (IOTN), yang terdiri dari dua komponen yaitu Aesthetic Component (AC) dan Dental Health Component (DHC).Penelitian dilakukan di SMA negeri 3 Tondano dengan jumlah siswa 390 orang.Pengambilan data dilakukan dengan pemeriksaan dan pengukuran menggunakan AC dan DHC. Hasil penelitian menunjukan bahwa berdasarkan AC 85,94% tidak/sedikit membutuhkan perawatan, 9,37% membutuhkan perawatan borderline dan 4,69% sangat membutuhkan perawatan, sedangkan berdasarkan DHC 51,56% tidak/sedikit membutuhkan perawatan, 35,94% membutuhkan perawatan borderline dan 12,5% sangat membutuhkan perawatan.Kata kunci: Maloklusi, Index Of Orthodontic Treatment Need, Aesthetic component, Dental Health Component.